LUNG CANCER - MIFTAH, HADEEL (faculty of applied basic medical science - Libyan international medical university, 2022)
Lung cancer, like all cancers, can act differently in each person, depending on the kind of lung cancer it is and the stage it is in, But when lung cancer spreads outside the lungs, it often goes to the same places, The first place lung cancer usually spreads to is the lymph nodes in the center of the chest. These lymph nodes are called mediastinal lymph nodes, Lung cancer may also spread to the lymph nodes in the lower neck. In its later stages, lung cancer may spread (metastasize) to distant parts of the body, like the liver, brain, or bones
Keywords: Lung cancer